The Interplay between Finasteride-Induced Androgen Imbalance, Endoplasmic Reticulum Stress, Oxidative Stress, and Liver Disorders in Paternal and Filial Generation - Sylwia Rzeszotek; Agnieszka Kolasa; Anna Pilutin; Kamila Misiakiewicz-Has; Katarzyna Sielatycka; Barbara Wiszniewska (Biomedicines, 2022)
Finasteride (Fin) causes androgen imbalance by inhibiting the conversion of testosterone (T) to its more active metabolite, dihydrotestosterone (DHT). Androgen receptors (AR) are present (e.g., in hepatocytes), which have well-developed endoplasmic reticulum (ERet). Cellular protein quality control is carried out by ERet in two paths: (i) unfolded protein response (UPR) and/or (ii) endoplasmic reticulum associated degradation (ERAD). ERet under continuous stress can generate changes in the UPR and can direct the cell on the pathway of life or death. It has been demonstrated that genes involved in ERet stress are among the genes controlled by androgens in some tissues. Oxidative stress is also one of the factors affecting the functions of ERet and androgens are one of the regulators of antioxidant enzyme activity. In this paper, we discuss/analyze a possible relationship between androgen imbalance in paternal generation with ERet stress and liver disorders in both paternal and filial generation. In our rat model, hyperglycemia and subsequent higher accumulation of hepatic glycogen were observed in all filial generation obtained from females fertilized by Fin-treated males (F1:Fin). Importantly, genes encoding enzymes involved in glucose and glycogen metabolism have been previously recognized among UPR targets.